Mediating Knowledge through Peer-to-Peer Interaction in a Multicultural Online Learning Environment: A Case Study of International Students in the US - Sadykova, Gulnara (International Review of Research in Open and Distributed Learning, 2014)
The continuous growth of online learning and its movement towards cross-border and cross-culture education has recently taken a new turn with the epic hype that currently surrounds the development of massive open online courses (MOOCs) (Beattie-Moss, 2013). This development brings to focus the experiences of international students who take online courses designed and offered within the paradigm of Western pedagogy. Employing a sociocultural theoretical framework (Vygotsky, 1978; Scollon & Scollon, 2001), this paper examines the mediating roles that peers may play in the context of multicultural online learning environments. This two-stage, mixed methods study explored the experiences of 12 international graduate students who took fully online courses in a large research university in the northeastern region of the United States. The data included a survey, online interviews, as well as a case study that took a close look at the experiences of a female student from China. Findings of the study demonstrated that international students that come from diverse native academic backgrounds and cultures may necessitate a close relationship with peers they meet in the US courses. Peers become invaluable mediators of knowledge for international students who seek peer assistance to compensate for the lack of culture-specific knowledge and skills and to satisfy their interest in the host culture. The study suggests that course developers and facilitators should be proactive when assigning group projects and activities so as to enable close peer-to-peer interaction and opportunities for building personal relationships with other class members.